The relationship between social determinants of health and the HIV/AIDS cases in children under 21: an integrative review (Research, Society and Development, 2020)
An integrative review was carried out in order to identify the social determinants of health linked to cases of Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV/AIDS) in children and adolescents described in ecological studies. The research was guided by the PICo strategy: What is the relationship between HIV/AIDS cases in children and adolescents about the social determinants of health described in national ecological studies? The search took place in January 2020, in the following databases: SciELO, LILACS, BDENF, MEDLINE, PubMed and Google Scholar, in Portuguese, English and Spanish. One article was identified that compounded the study sample, and the results showed the relationship of social determinants of health before HIV/AIDS cases, considering the following indicators: a) epidemiological (sex, age, year of diagnosis/notification, residence neighborhood); b) socioeconomic presented by ratio (of people responsible for the domicile; of appropriate housing; of people in the poverty range (with income of up to half a minimum wage); of illiterate people (number of people over 15 years who cannot read and write in their native language); of domiciles with an exclusive or sanitary bathroom and domiciles with seven or more residents). This study emphasized a correlation between the social determinants of health “poverty” and “illiteracy” with the incidence of HIV/AIDS in children and, moreover, that such social vulnerabilities can be risk factors for the vertical transmission of the infection. The need to conduct more scientific research on this subject is highlighted.